Observation of built-up edge formation on a carbide cutting tool with machining aluminium alloy under dry and wet conditions - Azlan, U. A. A.; Hadzley, M.; Tamin1, N. Fauzi; Noor, F. M.; Azhar, A. A.; Yusoff, M. Rahimi; Noriman, N. Z. (2017)
This paper presents the morphology of built-up edge (BUE) formation under wet and dry conditions with low and high cutting speeds. The workpiece materials and cutting tools selected for this work were aluminium alloy and canela carbide inserts graded PM25. The cutting tools underwent turning operation machining tests and their performance was evaluated by the flank wear and observation of the tool wear area. The machining tests were conducted at different spindle speeds and feed rates while the cut depth was kept constant. The analysis showed that formation of the BUE was dominant at low cutting speeds in dry conditions, but in wet conditions at high cutting speeds, a better performance was exhibited in terms of wear analysis.